2010
DOI: 10.1007/s11136-010-9725-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact and characteristics of quality of life in Japanese patients with multiple sclerosis

Abstract: Support for finding employment and having increased or maintained household income and readily available information about the disease contribute to improving QOL in Japanese MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 45 publications
0
29
0
1
Order By: Relevance
“…In fact, declining performance over time in tests for attention and verbal memory are predictive of impaired employment status, 13 which is important for maintaining patient quality of life (QOL). 14 The associations of MRI findings and social activities with cognitive function can vary among different ethnicities or countries, because cognitive impairment evaluated using BRB-N is influenced by several variables, such as age, sex and level of education. 15,16 In the present study, we aimed to evaluate the associations of MRI findings and working status with cognitive function in Japanese patients with MS.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, declining performance over time in tests for attention and verbal memory are predictive of impaired employment status, 13 which is important for maintaining patient quality of life (QOL). 14 The associations of MRI findings and social activities with cognitive function can vary among different ethnicities or countries, because cognitive impairment evaluated using BRB-N is influenced by several variables, such as age, sex and level of education. 15,16 In the present study, we aimed to evaluate the associations of MRI findings and working status with cognitive function in Japanese patients with MS.…”
Section: Introductionmentioning
confidence: 99%
“…The results highlighted that participants did not display any significant change in self-reported health-related quality-of-life during the initial 3-month transition period. Although health-related quality-of-life has been identified in the literature as a difficult domain to both measure and interpret given the subjective nature of the construct [32,33], the EQ-5D has been identified as a valid and reliable instrument when utilised in studies of individuals experiencing numerous health concerns [32][33][34]. Of importance to note in this study was that scores did not significantly improve between pre-discharge and post-discharge ratings for participants with ABI.…”
Section: Discussionmentioning
confidence: 77%
“…This confirms that while MS has low incidence compared to other neurological disorders, it can bring about a huge burden as it occurs at an early age. In the case of Japan whose epidemiological characteristics have the greatest similarity to those of Korea, its incidence is slightly higher than Korea's, but its prevalence is on the steady rise [12,33]. Given that Korea's domestic circumstances are similar, one can anticipate that MS will take up a higher portion of the entire burden of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Adjusted prevalence of MS in the United Kingdom (average latitude is 54.6 N) is 21 per 100,000, but 4 per 100,000 in northern Latin America (average latitude of 20.7 S) [2,9,10]. In Korea, Kim et al [11] reported 3.5 per 100,000 through national survey in 2006, which is one of the lowest in the world, even compared to that of the 3.9 in 100,000 in Morioka, Japan, located at the similar latitude in the neighboring country [12,13]. …”
Section: Introductionmentioning
confidence: 99%